Effect of expansive agents on the workability, crack resistance and durability of shrinkage-compensating concrete with low contents of fibers. (30th October 2020) - Pan, Zuanfeng; Zhu, Yazhi; Zhang, Defeng; Chen, Ning; Yang, Yichao; Cai, Xiaoning
Highlights: The effect of hybrid CaO- and ettringite- based expansive agents are investigated. The mechanical properties, crack resistance and durability of SHRCC are evaluated. Small-scale concrete slab tests are carried out to verify the use of SHRCC. The measure of expansion reinforcing band is validated against the member tests. Abstract: The effect of hybrid CaO- and ettringite-based expansive agents (HCSA) on the mechanical properties and durability of shrinkage-compensating concrete (SHRCC) is not well established. In this paper, SHRCC specimens were prepared incorporating with a high-performance calcium sulfoaluminate- hydrate calcium hydroxide expansive agent (HCSA) and three different types of fibers, i.e., polypropylene fiber (PP), polyvinyl alcohol fiber (PVA), and cellulose fiber (CF). The first part of the experimental program included material tests of the slump, compressive strength, restrained expansion ratio, early crack resistance, permeability and chloride penetration of SHRCC. The test results indicated that the HCSA-based SHRCC exhibited good workability, early crack resistance and durability. It is suggested that HCSA with a dosage of 7% − 8% of the weight of binder materials provided favorable shrinkage compensation and early crack resistance and had negligible impacts on the slump and compressive strength of the SHRCC. Although the content was low (approximately 0.7% by volume), PP fibers effectively improved the early crack resistance of the SHRCC. Adequate moist curing was also required to retain acceptable permeability and chloride penetration of the SHRCC. The second part of the experimental program involved tests on small-scale concrete basement slabs, which verified the effects of the expansive agent and fibers on the crack resistance of SHRCC at the component level.